Effect of extraction temperature on antimicrobial and antioxidant properties of Assam tea - Angana Payne Mandal; Mohd Hamza Hanfi; Lahari Saikia; Subhajyoti Deka; Shoma Paul Nandi (International Journal of Phytomedicine, 2014)
Tea is traditionally prepared by boiling dry leaves in water. This study was taken to evaluate the effect of extraction temperature on antimicrobial and antioxidant properties of Assam tea (Camellia sinensis var. assamica). Dry tea leaves were extracted in water at 4°C, 37°C and by boiling at 100°C, and antimicrobial as well as antioxidant activities of the extracts were compared. Antibacterial activity was determined by agar cup diffusion assay against two important pathogens; Staphylococcus aureus and Vibrio cholerae. Antioxidant property was monitored by total reducing power (TRP) assay, ferric reducing antioxidant power (FRAP) assay and 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) assay. Our results show that maximum antibiotic activities of the extracts are obtained by boiling tea leaves. We also show that boiling of tea leaves does not lead to loss of antioxidant properties.